2019
DOI: 10.1177/1756284819877788
|View full text |Cite
|
Sign up to set email alerts
|

Lifestyle intervention for gastroesophageal reflux disease: a national multicenter survey of lifestyle factor effects on gastroesophageal reflux disease in China

Abstract: Background: Poor habits can worsen gastroesophageal reflux disease (GERD) and reduce treatment efficacy. Few large-scale studies have examined lifestyle influences, particularly eating habits, on GERD in China, and research related to eating quickly, hyperphagia, and eating hot foods is quite limited. The aim of this study was to evaluate the relationship between GERD pathogenesis and lifestyle factors to produce useful information for the development of a clinical reference guide through a national multicente… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
57
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(67 citation statements)
references
References 39 publications
4
57
0
2
Order By: Relevance
“…In addition, smoking is also an established risk factor for GERD12. A recent study of 1518 tested subjects 31 has shown that smokers are 1.52 times more likely to develop GERD than non-smokers. However, it is unknown whether smoking cessation reduces the risk of GERD 12 .…”
Section: Discussionmentioning
confidence: 99%
“…In addition, smoking is also an established risk factor for GERD12. A recent study of 1518 tested subjects 31 has shown that smokers are 1.52 times more likely to develop GERD than non-smokers. However, it is unknown whether smoking cessation reduces the risk of GERD 12 .…”
Section: Discussionmentioning
confidence: 99%
“…The etiology of RE is multi-factorial. Lifestyle factors and eating habits such as smoking, drinking, preferences for high-fat and fried foods, and overeating are closely associated with RE [ 3 6 ]. In addition, it has been reported in the recent literature that mental disorders, especially anxiety and depression, are closely related to the onset and prognosis of RE [ 7 ], which seriously affects the quality of life of patients.…”
Section: Introductionmentioning
confidence: 99%
“…A regular smoker was defined as a person who smoked ⩾1 cigarette/day, for 6 months continuously or cumulatively, in accordance with World Health Organization (WHO) standards [3] .A drinker was defined as a person with a daily alcohol consumption level of >25 g for men or >15 g for women, for 6 months continuously or cumulatively, in accordance with the recommendations of the Chinese Ministry of Health [3] .…”
Section: Definitionsmentioning
confidence: 99%
“…Preference was defined as engaging in the habit >3 days/week, continuously or cumulatively for 6 months [3] . In this study, preference for strong tea (>3 g of tea), spicy foods.…”
Section: Definitionsmentioning
confidence: 99%
See 1 more Smart Citation